The Out of Court Divorce Model and Its Legal Implications: A Juridical Study in Babelan District Bekasi - Nursaidah Nursaidah; Adi Nur Rohman; Panti Rahayu (Universitas Islam Negeri Antasari Banjarmasin, 2020)
Abstract:Divorce in Indonesia, legally positive, must be carried out before a panel of judges at trial in accordance with the mandate of Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. However, out-of-court divorce is still common in several areas including Babelan district Bekasi where some of the community still practice out-of-court divorce. Out-of-court divorce even though it is considered religiously valid, leaves various legal issues such as neglect of the rights of children and wives who are divorced to the legality of the divorce itself. This study aims to find models of out-of-court divorce that are conducted by the community. Besides that, the study of the consequences and legal efforts to overcome this phenomenon are very important to be analyzed. This research is classified as a normative-empirical juridical study using a statutory approach assisted by a sociological approach. The results showed that research outside the court was carried out by: (1) kinship, and (2) through amil. From a positive legal perspective, divorce outside the court does not have a strong legal position, resulting in neglect of the right to support, distribution of assets and subsequent marriage.Keywords:divorce, Religious Court, legal consequences Abstrak:Perceraian di Indonesia secara hukum positif harus dilakukan dihadapan majelis hakim di persidangan sesuai dengan amanat Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Kompilasi Hukum Islam. Namun demikian, perceraian di luar pengadilan masih banyak ditemui di beberapa daerah termasuk di kecamatan Babelan Bekasi dimana sebagian masyarakatnya masih mempraktikkan perceraian di luar pengadilan. Perceraian di luar pengadilan meskipun dianggap sah secara agama, tetapi menyisakan berbagai persoalan hukum seperti pengabaian hak anak dan istri yang diceraikan hingga legalitas perceraian itu sendiri.Penelitian ini bertujuan untuk menemukan model-model perceraian di luar pengadilan yang dilakukan masyarakat. Disamping itu, kajian tentang akibat serta upaya hukum menanggulangi fenomena tersebut menjadi sangat penting untuk dianalisis. Penelitian ini tergolong penelitian yuridis normative-empiris dengan menggunakan pendekatan perundang-undangan dibantu dengan pendekatan sosiologis. Hasil penelitian menunjukkan bahwa penelitian di luar pengadilan dilakukan dengan cara: (1) secara kekeluargaan, dan (2) melalui amil. Dalam perspektif hukum positif, perceraian di luar pengadilan tidak memiliki kedudukan hukum yang kuat sehingga berakibat kepada pengabaian terhadap hak nafkah, pembagian harta serta pernikahan selanjutnya.Kata Kunci: akibat hukum, luar pengadilan, perceraian, Pengadilan Agama